QUALITY HEALTH SEED OATS-BLACK CV. COMMON SUBJECT TO DIFFERENT TREATMENTS - Barbieri, Marciele; Ávila, Viviane Schons de; Bovolini, Marcieli Pitorini; Muniz, Marlove Fátima Brião; Dörr, Andréa Cristina (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
The study investigated the effects of different treatments on seed health of black oat (Avena strigosa SCHREB). Seeds were subjected to the following treatments: witness, Vincit® 50 SC, Trichodel® + Vincit® 50SC, Trichodel®, control without treatment after they were packed in boxes gerbox substrate filter paper moistened with sterile distilled water. BOD remained in chambers at 25 º C, with a photoperiod of 12 hours until the evaluation. The seedborne fungi were identified with the aid of a stereoscopic microscope and optical after seven days of incubation. The statistical design was completely randomized with four treatments and eight replicates of 50 seeds each. The fungus Alternaria spp, Fusarium spp. Botrytis spp. Rhizoctonia spp. Phoma spp. and Trichoderma spp. were identified in Avena strigosa.Os results showed that the chemical (Vincit® 50SC), isolated or associated with Trichodel® was effective for the control of potentially pathogenic fungi for oat seeds.